Alpha-terpineol grafted acetylated lentinan as an anti-bacterial adhesion agent. (1st February 2022) - Ding, Qiang; Zhuang, Tingting; Fu, Pengcheng; Zhou, Qing; Luo, Lei; Dong, Zixuan; Li, Hang; Tang, Shunqing
Abstract: Biomedical implants-associated bacterial infections have become a major threat to human health. Therefore, it is meaningful to develop new antibacterial strategies to solve this problem. In this study, we conjugated acetylated lentinan (AceLNT) with α-terpineol (AceLNT-g-α-ter), a highly effective natural antibacterial compound, to constitute a novel AceLNT-g-α-ter membrane (AceLNT-g-α-terM). Compared with AceLNT membrane (AceLNTM), the adhesion amount of E. coli and P. aeruginosa in AceLNT-g-α-terM decreased by 80% and 85% after 7 d incubation in fluid bacterial medium. Moreover, the number of E. coli and P. aeruginosa biofilm on AceLNT-g-α-terM surface decreased by 70% and 71%. At the meanwhile, α-terpineol grafting modification of AceLNT had limited effect on its stimulating activity on macrophages and had no more cytotoxicity. In summary, our study firstly confirmed that AceLNT-g-α-terM could effectively inhibit gram-negative bacteria adhesion and biofilm formation, and provided a novel strategy for preventing infection of biomedical implants. Graphical abstract: Unlabelled Image Highlights: Alpha-terpineol grafted acetylated lentinan membrane as an anti-bacterial adhesion and anti-biofilm agent. AceLNT-g-α-terM exhibited anti-bacterial adhesion, anti-biofilm and immunostimulatory activity. AceLNT-g-α-terM performed no more cytotoxicity.